2006
DOI: 10.1002/bit.20751
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric reduction of α, β-unsaturated ketone to (R) allylic alcohol byCandida chilensis

Abstract: A pilot scale whole cell process was developed for the enantioselective 1,2-reduction of prochiral alpha,beta-unsaturated ketone to (R) allylic alcohol using Candida chilensis. Initial development showed high enantiomeric excess (EE > 95%) but low product yield (10%). Process development, using a combination of statistically designed screening and optimization experiments, improved the desired alcohol yield to 90%. The fermentation growth stage, particularly medium composition and growth pH, had a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…Their development towards large-scale use would be improved with the establishment of a high-throughput screening system, which already exists for ketoreductases. [36] Regarding the specificity of these enzymes, tests with selected products of the ER reaction revealed that, while the carbonyl group was not reduced, additionally present double bonds could be further reduced and form unwanted side products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their development towards large-scale use would be improved with the establishment of a high-throughput screening system, which already exists for ketoreductases. [36] Regarding the specificity of these enzymes, tests with selected products of the ER reaction revealed that, while the carbonyl group was not reduced, additionally present double bonds could be further reduced and form unwanted side products.…”
Section: Discussionmentioning
confidence: 99%
“…The latter employ the same cofactor, NAD(P)H, to reduce the carbonyl function, which can lower selectivity and produce additional impurities. [36,37] The use of isolated enzymes can circumvent this problem but still requires a cofactor regeneration system. Importantly, both ER and the regenerating enzyme have to be active at the same pH range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, the whole-cell catalyzed reduction of ␣,␤-unsaturated carbonyl compounds can be complex and hampered by competing enzymatic reactions (8). Thus, in the asymmetric bioreduction of citral to the ␣,␤-saturated aldehyde citronellal, the undesirable by-products nerol, geraniol, and citronellol were formed due to the action of competing alcohol dehydrogenases and citral lyase activity (9); in stereoselective biocatalytic reduction of ␣-ionone by Glomerella cingulata, (6S,9R)-␣-ionol was produced, some of which was subsequently hydrogenated by enoate reductase to form (6S,9R)-7,8-dyhidro-␣-ionol (10); and with use of ␣,␤-unsaturated aldehydes as the substrate, the aldehyde oxidation catalyzed by aldehyde dehydrogenase usually led to the formation of undesirable ␣,␤-unsaturated carboxylic acids (11,12).…”
mentioning
confidence: 99%
“…They display different physical and enzymatic properties, show a wide variety of substrate specificities, and are mainly classified into three superfamilies, zinc-dependent alcohol dehydrogenases, short-chain dehydrogenase/reductases (SDRs), and aldo-keto reductases, based on their catalytic properties and sequence information (8,14,32). Among the various enzyme sources, Candida species are attractive as highly stereospecific oxidoreductase donors (4,13,15,16,25,30). In many cases, the stereospecific oxidoreductases from strains of the genus Candida are dissimilar in structure and classified in different superfamilies (15,16,38).…”
mentioning
confidence: 99%